Honoring our teachings: children’s storybooks as indigenous public health practice - Maudrie, Tara L.; Grubin, Fiona; Conrad, Maisie; Velasquez Baez, Jocelyn; Saniguq Ullrich, Jessica; Allison-Burbank, Joshuaa; Martin, Lisa; Austin, Crystal; Joyner, Joelle; Ronyak, Marcella; Masten, Kristin; Ingalls, Allison; et al. (Frontiers in Public Health, 2024)
Introduction American Indian and Alaska Native (AIAN) communities continue to flourish and innovate in the face of the COVID-19 pandemic. Storytelling is an important tradition for AIAN communities that can function as an intervention modality. To support the needs of AIAN children and caregivers, we (a collaborative workgroup of Indigenous health researchers) developed a culturally grounded storybook that provides pandemic-related public health guidance and mental health coping strategies woven with Inter-Tribal values and teachings. Methods A collaborative workgroup, representing diverse tribal affiliations, met via four virtual meetings in early 2021 to discuss evolving COVID-19 pandemic public health guidance, community experiences and responses to emerging challenges, and how to ground the story in shared AIAN cultural strengths. We developed and distributed a brief survey for caregivers to evaluate the resulting book. Results The workgroup iteratively reviewed versions of the storyline until reaching a consensus on the final text. An AI artist from the workgroup created illustrations to accompany the text. The resulting book, titled Our Smallest Warriors, Our Strongest Medicine: Honoring Our Teachings during COVID-19 contains 46 pages of text and full-color illustrations. An online toolkit including coloring pages, traditional language activities, and caregiver resources accompanies the book. We printed and distributed 50,024 physical copies of the book and a free online version remains available. An online survey completed by N = 34 caregivers who read the book with their child(ren) showed strong satisfaction with the book and interest in future books. Discussion The development of this storybook provides insights for creative dissemination of future public health initiatives, especially those geared toward AIAN communities. The positive reception and widespread interest in the storybook illustrate how braiding AIAN cultural teachings with public health guidance can be an effective way to disseminate health information. This storybook highlights the importance of storytelling as an immersive learning experience through which caregivers and children connect to family, community, culture, and public health guidance. Culturally grounded public health interventions can be effective and powerful in uplifting AIAN cultural values and promoting health and well-being for present and future generations.